(untitled) (Fiep Bulletin - online, 2013)
Over the years, human beings will change the natural aging process. Thus, functional and structural changes occur in the body due to the sensory diseases, bone, cardiovascular and diabetes. The main cause that limits the life of the elderly is imbalance, a factor that has not always specific cause, but showing commitment of the entire system. Thus, most cases of imbalance begins between ages 65 and 75 years. This research aims to evaluate the influence of plantar sensitivity in balance physically active elderly. The sample comprises of 86 adults of both genders with a mean age of 65.31 years physically active. During data collection, subjects were evaluated for their sensitivity to plant and balance through Estesiômetro Kit (Semmes-weinstein Mono filaments) and, static balance test. Results in no observed relationship between sensitivity and balance, unlike the results of other similar items. We conclude that it is important to conduct further studies to identify possible factors that can alter the levels of sensitivity and balance this public.